CERTAIN PSYCHOMETRIC INDEXES DYNAMICS IN THE GROUPS OF PATIENTS WITH PAIN FORM OF CHRONIC ISCHEMIC HEART DISEASE WITH A PRESENCE OR ABSENCE OF DEPRESSION ON THE STANDARD THERAPY STAGES - Kulik, A.L.; Serikova, O.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The study of anxiety and depression levels changes in comparison to QoLI and clinical indexes in patients with the pain form of chronic IHD with a presence or absence of depression on the stages of therapy is conducted. In all 103 patients were looked after in age 48,6±7,5. Patients, depending on the presence of depression, were parted on 2 groups. Initially in the group of patients with depression were marked increased level of anxiety, the QoLI decline, increase of mean values of stenocardia and heart failure FC, frequencies and the AH burden, on comparison with a group without depression. The standard IHD therapy improves the clinical being of patients in both groups, promoting QoLI, bringing the stenocardia and heart failure FC and diminishing the level of depression and anxiety. Thus at the patients IHD with concomitant depression as standard therapy results the change of depression, anxiety, QoLI levels and clinical status are expressed in less degree, not achieving the indexes got in the group of patients without depression. Persistent distinctions between groups testifies to the necessity of antidepressants addition to standard therapy.